The Use of Drama To Reduce English Speaking Anxiety of Informatics Engineering Students At Uniks - Chairani, Sri; Fitriani, Rahmah; Mukminin, Amirul; Matondang, Saiful Anwar (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
Speaking is one of the most important aspects of learning a second or foreign language. Anxiety is one of the affective factors that influence success in learning English, especially in speaking. The reason for  excessive fear or anxiety in speaking the English language are the fear of making mistakes, the fear of embarrassing oneself, the fear of being laughed, the fear of getting more question from other students, and the fear of standing in front of the class. This study discuss about the use of drama to reduce English speaking anxiety of informatics engineering students at UNIKS. The aim of this study is to find out how anxiety affects the speaking skills of informatics engineering students at UNIKS, and to observe how the drama is effectively solve the anxiety problem to improve the speaking skill of informatics engineering students at UNIKS. A mixed-methods research design was employed, combining quantitative and qualitative data collection and analysis.The results show that drama is effective in reducing the anxiety of the informatics engineering students at UNIKS in speaking English.